Menangkal Radikalisme Agama Di Sekolah - Munip, Abdul (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2012)
It is undeniable that some of Indonesian Muslims understand Islam in radicalism perspective. They used several of means to disseminate this radicalism through organization of cadres, speeches in mosques are managed by their control, publishing magazines, booklets and books, and through various websites on the internet. As a result, Islamic radicalism has entered the most schools in some areas. If this is not immediately anticipated, it can help in growing the intolerance attitudes among students as opposed to the purpose of religious education itself.